Sensors and Communications for the Social Good - Palazzi, Claudio; Gaggi, Ombretta; Manzoni, Pietro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Social good is typically defined as an actions and services that benefit the general public. In this case, internet connection, education, and healthcare are all good examples of social goods. However, new media innovations and the explosion of online communities have added new meaning to the term. Social good is now about global citizens uniting to unlock the potential of individuals, technology, and collaboration to create a positive societal impact.